MANAGEMENT ETHICS IN THE AI-ART ECOSYSTEM - Jadhav , Ragini Kunal; Traisa, Dr. Roopa; Farooqui, Yassir; Mary, V. Sheela; Nanda, Simranjeet; Sohal, Jagmeet (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The creativity, ownership and ethics of the art ecosystem has been re-defined in a manner that has never before been witnessed due to the fast changing nature of the artificial intelligence (AI) inside the art ecosystem. The problem that the ethics of management in this new domain deals with is the balancing of innovation and moral responsibility, to achieve transparency, fairness, and respect of the human beings and creative integrity. Ethical management should encompass the issue of authorship, intellectual property and accountability in instances whereby the art pieces generated by the AI system are raising issues of originality. The AI application in art production or curation by organizations is met with the issues of algorithmic bias, cultural appropriation, and relegation of human artists. Effective management operations should be inclusiveness, approval and equitable allocation of credit to contributors of human and machine resources. Additionally, ethical leadership should be attentive to data integrity as well as not to reproduce copyrighted material without permission. Transparency in the use of AI tools and the creative process is the key to the assurance of trust and integrity of the people to the art. Making its way through the socio-economic consequences, including the labor migration, and the commercialization of AI art, the management also should. By establishing robust ethical norms and building accountability, managers would have an opportunity to develop a sustainable, human-based innovation that would appreciate technological growth and artistic heritage within the dynamic AI-art ecosystem.